Polymeric membranes for desalination using membrane distillation: A review - Ravi, J. (Elsevier B.V., 2020)
Membrane distillation (MD) is a burgeoning membrane technology that has gained immense interest among membrane scientists worldwide. Despite a slow start, both the theoretical and experimental researches on MD, especially on desalination applications, have escalated significantly over the past few decades. Although the large-scale use of MD has not proliferated worldwide, the researches done thus far have helped us to understand the rudiments of MD and explore the potential areas capable of enhancing its commercial attractiveness. Membranes of very high quality, nearing the properties of an ideal membrane, will fuel the growth of this technology. An ideal membrane for MD is expected to have features such as high liquid entry pressure, low fouling rate, low thermal conductivity, high permeability and excellent mechanical strength. In that regard, ceramic membranes have been appreciated for their high tolerance to harsh conditions, however, their high cost has rendered them less favourable commercially. Polymeric membranes are seen as a plausible cheaper alternative and have dominated research done thus far on MD. This review aims to give a brief introduction to MD and a summary of the research efforts to acquire the desired properties in polymeric membranes used in MD for desalination purposes. Potential research directions are highlighted too. Â© 2020 Elsevier B.V.